The public health risk posed by Listeria monocytogenes in frozen fruit and vegetables including herbs, blanched during processing. (20th April 2020) - ,; Koutsoumanis, Konstantinos; Alvarez‐Ordóñez, Avelino; Bolton, Declan; Bover‐Cid, Sara; Chemaly, Marianne; Davies, Robert; De Cesare, Alessandra; Herman, Lieve; Hilbert, Friederike; Lindqvist, Roland; Nauta, Maarten; et al.
Abstract: A multi‐country outbreak of Listeria monocytogenes ST6 linked to blanched frozen vegetables (bfV) took place in the EU (2015–2018). Evidence of food‐borne outbreaks shows that L. monocytogenes is the most relevant pathogen associated with bfV. The probability of illness per serving of uncooked bfV, for the elderly (65–74 years old) population, is up to 3, 600 times greater than cooked bfV and very likely lower than any of the evaluated ready‐to‐eat food categories. The main factors affecting contamination and growth of L. monocytogenes in bfV during processing are the hygiene of the raw materials and process water; the hygienic conditions of the food processing environment (FPE); and the time/Temperature (t/T) combinations used for storage and processing (e.g. blanching, cooling). Relevant factors after processing are the intrinsic characteristics of the bfV, the t/T combinations used for thawing and storage and subsequent cooking conditions, unless eaten uncooked. Analysis of the possible control options suggests that application of a complete HACCP plan is either not possible or would not further enhance food safety. Instead, specific prerequisite programmes (PRP) and operational PRP activities should be applied such as cleaning and disinfection of the FPE, water control, t/T control and product information and consumer awareness. The occurrence of low levels of L. monocytogenes at the end of the production process (e.g. < 10 CFU/g) would be compatible with the limit of 100 CFU/g at the moment of consumption if any labelling recommendations are strictly followed (i.e. 24 h at 5°C). Under reasonably foreseeable conditions of use (i.e. 48 h at 12°C), L. monocytogenes levels need to be considerably lower (not detected in 25 g). Routine monitoring programmes for L. monocytogenes should be designed following a risk‐based approach and regularly revised based on trend analysis, being FPE monitoring a key activity in the frozen vegetable industry.